2021
DOI: 10.3762/bjnano.12.23
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, bio-uptake and toxicity of polymer-coated silver nanoparticles and their interaction with human peripheral blood mononuclear cells

Abstract: Silver nanoparticles (AgNPs) are widely used in medical applications due to their antibacterial and antiviral properties. Despite the extensive study of AgNPs, their toxicity and their effect on human health is poorly understood, as a result of issues such as poor control of NP properties and lack of proper characterization. The aim of this study was to investigate the combined characterization, bio-uptake, and toxicity of well-characterized polyvinylpyrrolidone (PVP)-coated AgNPs in exposure media during expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…It is important to note that when using the developed technique of 10-fold cyclic freezing/thawing for individual specific fibers, for example, sericin-containing ones, it is possible to achieve the predominant formation of AgNPs with a diameter of less than 6 nm (up to 96.7%), which undoubtedly increases the possibility of regulating the size of nanoparticles on medical devices, expanding the possibilities of their application in practice [ 58 , 60 , 61 ], including increasing the antibacterial activity [ 62 ] due to their better stability and high biocompatibility with sericin.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that when using the developed technique of 10-fold cyclic freezing/thawing for individual specific fibers, for example, sericin-containing ones, it is possible to achieve the predominant formation of AgNPs with a diameter of less than 6 nm (up to 96.7%), which undoubtedly increases the possibility of regulating the size of nanoparticles on medical devices, expanding the possibilities of their application in practice [ 58 , 60 , 61 ], including increasing the antibacterial activity [ 62 ] due to their better stability and high biocompatibility with sericin.…”
Section: Discussionmentioning
confidence: 99%
“…albicans ), destruction of the mitochondrial respiratory chain and increase in ROS production destroy DNA structure. Another study evaluated the uptake and cytotoxicity of Ag NPs in human peripheral blood mononuclear cells (PBMCs) using polyvinylpyrrolidone-coated Ag NPs and AgNO 3 controls and observed that compared with controls, Ag NPs were more toxic to PBMCs when normalised to the amount of cell-associated Ag (Pourhoseini et al 2021 ). Although higher concentrations of Ag NPs are advised for therapeutic applications, it contradicts the obtained toxicity data (Rajan et al 2022 ).…”
Section: Characteristics Of Nps Against Fungal Infectionmentioning
confidence: 99%
“…Recently, cytotoxicity studies of different AgNPs [47] and SiO 2 NPs [48] on lymphocytes and monocytes from human blood (PBMC) have been reported as model biocompatibility assays. For this reason, the interaction of bioHNPs with PBMC was assessed by means of flow cytometry as a complementary in vitro study of the biocompatibility of these NPs.…”
Section: Tablementioning
confidence: 99%